Dust Observations by the Radio and Plasma Wave Science Instrument During Cassini's Grand Finale. Issue 19 (4th October 2018) - Ye, S.‐Y.; Kurth, W. S.; Hospodarsky, G. B.; Persoon, A. M.; Sulaiman, A. H.; Gurnett, D. A.; Morooka, M.; Wahlund, J.‐E.; Hsu, H.‐W.; Sternovsky, Z.; Wang, X.; Horanyi, M.; et al.
Abstract: Dust particles in the Saturn system can be detected by the Radio and Plasma Wave Science (RPWS) instrument on board Cassini via antenna voltage signals induced by dust impacts. These impact signals have been simulated in the laboratory by accelerating dust particles onto a Cassini model with electric field antennas. RPWS dust measurements have been shown to be consistent with the Cosmic Dust Analyzer. During the Grand Finale orbits, Cassini flew through the gap between the D ring and Saturn's atmosphere 22 times. In situ measurements by RPWS helped quantify the hazards posed to the spacecraft and instruments on board, which showed a micron‐sized dust density orders of magnitude lower than that observed during the Ring Grazing orbits. Close inspection of the waveforms indicated a possible dependence of the impact signal decay time on ambient plasma density. Plain Language Summary: Cassini flew through the gap between Saturn and its rings for 22 times before plunging into the atmosphere of Saturn, ending its 20‐year mission. The radio and plasma waves instrument on board Cassini helped quantify the dust hazard in this previously unexplored region. The measured density of large dust particles was much lower than expected, allowing high‐value science observations during the subsequent Grand Finale orbits. Key Points: Cassini detected few micron‐sized particles near the ring plane between Saturn and the D ring RPWS measured the dust density profile and size distribution at the edge of the D ring Waveforms of the dust impact signals change with the background plasma density